Microbiologic and clinical characteristics of biofilm-forming Candida parapsilosis isolates associated with fungaemia and their impact on mortality. (July 2018) - Soldini, S.; Posteraro, B.; Vella, A.; De Carolis, E.; Borghi, E.; Falleni, M.; Losito, A.R.; Maiuro, G.; Trecarichi, E.M.; Sanguinetti, M.; Tumbarello, M.
Abstract: Objectives: Biofilm formation (BF) by fungal isolates may dramatically complicate infection. We determined the ability of Candida parapsilosis isolates from single fungaemia episodes to form biofilms and we analysed biofilm subgroups for antifungal susceptibility and pathogenic potential. We then correlated BF with clinical characteristics and outcomes of the episodes. Methods: BF was measured using the crystal violet biomass assay. Antifungal susceptibility of preformed biofilms was assessed, and virulence was studied using the Galleria mellonella model. A retrospective analysis of patients' clinical records was performed. Results: Of 190 patient-unique isolates, 84, 38 and 68 were identified as having high BF (HBF), moderate BF (MBF) or low BF (LBF), respectively. Among 30 randomly selected isolates, nine (eight HBF and one MBF), six (all HBF) and one (HBF) isolates had elevated sessile minimum inhibitory concentrations to fluconazole, anidulafungin or amphotericin B; all HBF and MBF isolates had elevated voriconazole sessile minimum inhibitory concentrations. G. mellonella killing rates of HBF isolates were significantly greater than MBF (or LBF) isolates (50% vs. 20%, 2 days from infection). By comparing HBF/MBF (106 patients) and LBF (84 patients) groups, we found that HBF/MBF patients had more central venous catheter-related fungaemias (62/106 (58.5%) vs. 29/84 (34.5%), p 0.001) and were more likely to die at 30 days from fungaemia onset (61/106 (57.5%) vs. 28/84 (33.3%), p 0.01). In the HBF/MBF group, azole antifungal therapy and central venous catheter removal were significantly associated with a higher and lower 30-day mortality rate, respectively. Conclusions: C. parapsilosis BF influences the clinical outcome in patients with fungaemia.